Comportamiento Productivo y Reproductivo de Hembras Bovinas Holstein en la Sociedad de hecho Agrícola y Ganadera San Pablo M-D. - Brito Pérez, Víctor Alfonso. (2018)
The research was developed in the productive entity "Society of fact agricultural and cattle raising San Pablo MD", from the province of Tungurahua, county of Ambato, Cunchibamba Parish, with the objective of evaluating the productive and reproductive behavior of bovine Holstein females, under the conditions of the study area, using the records corresponding to the period 2015 - 2017 of the total herd of Holstein bovine females (48 animals). The herd evaluated constitutes of 63% animals in production, of which 37% belong to other breeds such as Brown Swiss, Jersey and F1 (Holstein x Jersey, Holstein x Brown Swiss). For the productive evaluation the variables were considered as; duration of lactation, production of real lactation, daily production and reproductive evaluation parameters such as; duration of gestation, interval between deliveries, dry period, open days and number of services by conception based on regression analysis and descriptive statistics. Milk production (total averages) was 5352.92 ± 807.18 lt / cow, in lactation of 309.06 ± 44.83 days. The average daily production behaved at about 17.32 ± 1.26 lt / cow. The duration of pregnancy was recorded at 280.24 ± 4.16 days. The interval between deliveries in the period evaluated was 393.92 ± 25.92 days; the dry period of 74.09 ± 26.97 days; the days open was 107.36 ± 25.30; the number of services per conception was 1.7. The evaluation of milk quality showed normal values, except in the range of protein and total bacteriological count (CBT), mainly associated with contamination due to the lack of asepsis and inadequate handling during the execution of the milking routine. There are evidences of affected production, far from the averages established for the breed, being able to increase with an efficient management.